2013 IEEE International Symposium on Industrial Electronics 2013
DOI: 10.1109/isie.2013.6563858
|View full text |Cite
|
Sign up to set email alerts
|

Design of the battery management system of LiFePO<inf>4</inf> batteries for electric off-road vehicles

Abstract: This paper describes the design of a modular battery management system for electric off-road vehicles, where lithiumion batteries are expected to be widely used. A massive electrification of off-road vehicles can be enabled by the availability of a standard battery module, provided with an effective management unit. The design and some preliminary experimental results of the module management unit are discussed in this paper. The unit contains a high current active equalizer that enables the dynamic charge equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…A proper battery management system (BMS) with active balancing was developed by the University of Pisa in cooperation with ENEA [3], [6], [7]. It provides the functions of protection, monitoring, data acquisition and active balancing of the state of charge of the cells.…”
Section: Battery Management Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A proper battery management system (BMS) with active balancing was developed by the University of Pisa in cooperation with ENEA [3], [6], [7]. It provides the functions of protection, monitoring, data acquisition and active balancing of the state of charge of the cells.…”
Section: Battery Management Systemmentioning
confidence: 99%
“…A diesel engine commonly powers off-road vehicles. The replacement or the combination of the internal combustion engine with an electric motor might be a remarkable step toward energy sustainability by reducing CO 2 emissions and by improving energy utilization efficiency [1] [2] [3]. A recent study made by ENEA on the Italian market for mobile work machines gives a good idea of the relevance of these kinds of vehicles and the impact of their electrification [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an emphasized interest for lithium ion (Li-Io) batteries has been registered due to their high potentialities not only as electrical sources for electric vehicles, but also as storage systems in smart grid environment and naturally as support technology for communication systems [1][2][3][4][5]. Moreover, many studies showed that well-established statistical methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to battery design, many approaches have been proposed in the relevant literature [1][2][3][4][5][7][8][9][10]. However, due to the large number of factors involved, many difficulties persist to solve the problem of the battery size optimization over a prefixed time horizon of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The standard module has a 12.8 V nominal voltage. Its implementation with three capacity values: 30, 60, and 100 Ah is reported in [7].…”
Section: Introductionmentioning
confidence: 99%